Advocating for a Child-Centric Approach: Indonesian Jurisdiction in Cross-Border Surrogacy - Komalasari, Rita; Mustafa, Cecep (Jurnal Negara Hukum: Membangun Hukum Untuk Keadilan, 2024)
This article aims to address gaps in national policy by analyzing the complex interactions between international law, Indonesian jurisdiction, and child welfare in cross-border surrogacy arrangements. It advocates for prioritizing the best interests of children and offers practical recommendations for stakeholders involved in cross-border surrogacy. The research examines the principles and framework established by the Hague Conference on Private International Law and their implications within the Indonesian context. It also explores domestic Indonesian law, court decisions, and ethical dilemmas surrounding cross-border surrogacy. This article provides insight and perspective on the ongoing discussion of cross-border surrogacy by filling gaps identified in the literature. The analysis highlights the importance of children’s interests in cross-border surrogacy cases, offers a detailed examination of the role of Indonesian courts, and integrates ethical considerations into the legal framework. The research culminates in practical policy recommendations for policymakers, legal practitioners, and other stakeholders, with the ultimate goal of protecting and enhancing the well-being of children born through these complex arrangements. The findings emphasize the importance of prioritizing children’s well-being, recognizing them not simply as objects but as individuals with inherent rights, identities, and needs that require protection.